2022
DOI: 10.3390/molecules28010295
|View full text |Cite
|
Sign up to set email alerts
|

Screening and Identification of Anti-Inflammatory Compounds from Erdong Gao via Multiple-Target-Cell Extraction Coupled with HPLC-Q-TOF-MS/MS and Their Structure–Activity Relationship

Abstract: Erdong Gao (EDG), consisting equally of roots of Asparagi Radix and Ophiopogonis Radix, is a well-known traditional Chinese formulation that has been used to treat cough and throat pain for centuries. However, the bioactive components in EDG remain to be elucidated. In this study, a rapid and effective method involving live cell bio-specific extraction and HPLC-Q-TOF-MS/MS was established to rapidly screen and identify the anti-inflammatory compounds of an EDG extract. One hundred and twenty-four components we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Additionally, research has demonstrated that the chemical constituents of phenolic acids possess strong antioxidant capacity. 24,25 It exhibits antioxidant, antiinflammatory, antitumor, and other pharmacological effects, which may be linked to the content and type of phenolic acids present in T. hemsleyanum . Polysaccharide is also a crucial active compound in T. hemsleyanum and is one of its saccharides.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, research has demonstrated that the chemical constituents of phenolic acids possess strong antioxidant capacity. 24,25 It exhibits antioxidant, antiinflammatory, antitumor, and other pharmacological effects, which may be linked to the content and type of phenolic acids present in T. hemsleyanum . Polysaccharide is also a crucial active compound in T. hemsleyanum and is one of its saccharides.…”
Section: Resultsmentioning
confidence: 99%
“…Ultra-performance liquid chromatography-tandem quadrupole-time-of-flight mass spectrometry (UPLC-Q-TOF-MS E ) is a useful method for this purpose due to its high sensitivity, selectivity, and ability to provide complete and high-quality mass spectrometry data. 4,5 This method is simple and efficient 6,7 and has been successfully applied in many fields, 8 including Chinese herbal medicine, 912 natural product research and development, 13,14 microorganisms, 15 and the food industry. It serves as a highly effective tool for elucidating the chemical composition profile of substances.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, structures containing two or more sugar chains at the C-3 position (especially the additional rhamnose units), ,, and the 25­( R / S )-configuration (25 R > 25 S : A549, Caski, HepG2, and MCF-7; , 25 S > 25 R : BEL-7402, HT-29, Hela, MDA-MB-468, BT549, and SW620 cell lines , ) were considered important for cytotoxicity. Moreover, the aforementioned factors also influenced anti-inflammatory, antiatherosclerotic, antidiabetic, and antiosteosarcoma activities. However, studies of oat saponins, including the new saponins identified in this study, are still lacking.…”
Section: Furostane Saponinsmentioning
confidence: 99%